Supervisi Pembelajaran Kepala Madrasah Dalam Pelaksanaan Kurikulum 2013 Dengan Multiple Intellegences Dan Emotional Intelligence Pada Madrasah Ibtidaiyah - Ali, Nur (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2014)
One of the principal’s responsibility as an instructional supervition toward the teachers at Islamic Secondary School (Madrasah Ibtidaiyah) is to improve teacher’s competencies in implementing thematic-scientifi approach in teaching learning process. Supervisor must held supervition well.Generally the principals of Madrasah as supervisor had not implemented the principles of supervitin yet in implementing an instructional supervition. Beside that he/she didnot also used persuasive approach. Therefore toimprove the quality of persuasive, the supervisor should to understand about multiple intellegences dan belong to hight Emotional Intelligence becouse the activities of supervition were related to the oportunity of the teachers and students to develop the interest, talent and social interaction beetwen supervisor and teachers of islamic secondary school. This article is to describe about the principal instructional supervition of islamic secondary school (ISS) in implementing the curriculum 2013 with using multiple intellegences and emotional intelligence at ISS. ThePrincipal of Islamic Secondary School who had understood the multiple intellegences well and belong to the hight emotional Intelligence more success in implementing instructional supervition and be able to develop the interpersonal, intrapersonal intellegences and can also develop selfmotivation and the teachers of ISS to implement thematic-scientifi approach well.Key Word: Thematic, saintifi, multiple intellegences, Emotional Intelligence, Instructional supervition.